The Implementation of Buen Vivir in Ecuador: An Analysis of the Stakeholders’ Discourses - Marchand, Lucile; Hérault, Mathilde (European Journal of Sustainable Development, 2019)
Buen vivir is a central notion in Ecuador and was introduced in its Constitution in 2008. On the individual level, this notion describes a multidimensional form of well-being, integrating strong cultural and ecological aspects based on indigenous communities’ knowledge. On the national scale, buen vivir is the key notion of public policies and justifies an intervention of the state in all dimensions of sustainable development. The implementation of buen vivir in a developing country as Ecuador raises questions about multiple social and economic aspects. The aim of this paper is to identify all of these challenges that such a transition implies. To do so, this paper uses a qualitative and multidimensional approach based on 40 semi-directive interviews with stakeholders of the policy implementation of buen vivir. The interview grid was divided into four parts: (i) individual characteristics, (ii) definition and implementation of buen vivir, (iii) the extractivism in Ecuador and (iv) the challenges of the transition between two models of development. The preliminary results identify two major challenges. Firstly, the main challenge is the governance of this major transition and the issue of corruption in Ecuador. Secondly, these interviews show that education is the most central dimension to implement buen vivir correctly. Keywords: Buen vivir, discourse’s analysis, extractivism